Pengaruh Sales Promotion, Fashion Involvement, dan Hedonic Shopping Motivation terhadap Impulsive Buying pada Konsumen Rabbani di Semarang - Nur Lia Hadi Muhiroh; Imam Nuryanto (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
The growing tendency of consumers to engage in impulsive purchases of fashion products presents a compelling subject for further research. This study aims to examine the influence of sales promotion, fashion involvement, and hedonic shopping motivation on impulsive buying among Rabbani consumers in Semarang, Indonesia. A quantitative research approach was employed, employing multiple linear regression analysis as the primary method. The sample comprised 120 respondents selected through purposive sampling based on predetermined criteria. The results indicate that sales promotion and hedonic shopping motivation exert a positive and significant influence on impulsive buying behavior, whereas fashion involvement does not have a statistically significant effect